Specific characteristics of piano interpretation by Alfred Cortot and our understanding of it - Gadzheva, Aleksandra (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The report looks at the position of the pianist Alfred Cortot (1877 – 1962), a notable figure in the musical art, in the field of musical interpretation. By marking her analysis with milestones from the life and artistic career of Cortot, the author presents an overview of the book „Cours d‘interprétation“ (1934). From a distance of 85 years from its original edition and 60 years from its publication in Bulgarian (translated into Bulgarian) and through her own viewpoint, she sets apart Cortot’s views in parallel with modern trends in musical interpretation. Also, the report discusses the compositional system, compositional and performance practice system, genre and stylistic specifics.